2007
DOI: 10.1136/ard.2006.062042
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic lymphoid neogenesis in psoriatic arthritis

Abstract: Background: Ectopic lymphoid neogenesis (LN) occurs in rheumatoid synovium, where it is thought to drive local antigen-dependent B cell development and autoantibody production. This process involves the expression of specific homing chemokines and the development of high endothelial venules (HEV). Objective: To investigate whether these mechanisms occur in psoriatic arthritis (PsA) synovium, where autoantibodies have not been described and the organisation and function of B cells is not clear, and to analyse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
112
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 35 publications
14
112
3
1
Order By: Relevance
“…1B), independently of potentially confounding factors such as the MHC background (HLA-DR shared epitope) and the presence of intracellular citrullinated proteins (data not shown) (31,32). These data confirm and extend our previous observations (26,28) showing that ectopic lymphoid neogenesis in the synovial membrane is neither restricted to nor preferentially associated with autoantibody positive rheumatic conditions.…”
Section: Synovial Lymphoid Neogenesis Is Not Restricted To Rasupporting
confidence: 80%
See 1 more Smart Citation
“…1B), independently of potentially confounding factors such as the MHC background (HLA-DR shared epitope) and the presence of intracellular citrullinated proteins (data not shown) (31,32). These data confirm and extend our previous observations (26,28) showing that ectopic lymphoid neogenesis in the synovial membrane is neither restricted to nor preferentially associated with autoantibody positive rheumatic conditions.…”
Section: Synovial Lymphoid Neogenesis Is Not Restricted To Rasupporting
confidence: 80%
“…Moreover, we recently demonstrated that B cell depletion by Rituximab decreased synovial tissue infiltration as well as lymphoid neogenesis after 16 wk of treatment (48). Taken together with the coexistence of different degrees of lymphoid organization in a single sample (23,26), these data indicate that synovial lymphoid neogenesis is a dynamic process which could be related to inflammation rather than a fixed pathological feature committed to specific B cell autoantigens. In SLO, Ag-driven B cell responses require the full maturation of lymphoid structures toward GC-reactions, a complex process orchestrated by lymphoid chemokines and cytokines (49,50) Defective expression of these mediators leads to abortive follicle formation and impaired B cell responses (49,51).…”
Section: Discussionmentioning
confidence: 76%
“…Synovial tissue biopsy samples were processed and evaluated for lining layer thickness, vascularity, global inflammatory infiltration, and lymphoid aggregates, as described previously (35)(36)(37). Synovial tissues from the 158 RA patients were divided into 2 groups.…”
Section: Methodsmentioning
confidence: 99%
“…B cells and plasma cells are found in the involved peripheral synovium of SpA patients with peripheral synovitis (3,4) as well as in the subchondral bone marrow of patients with axial SpA (5). The B cell infiltration in SpA patients with peripheral synovitis is often organized in aggregates (6,7) and, even if germinal center-like features remain rare, can display molecular features of antigen-driven clonal B cell expansion (8,9). Besides this indirect evidence from immunopathologic studies, a direct functional role of B cells in SpA pathogenesis is suggested by the contribution of humoral immunity to versican in the induction of experimental spondylitis and sacroiliitis in BALB/c mice (10).…”
mentioning
confidence: 99%